The importance of market integration and self-consumption for the food safety of family farmers: an analysis in the municipality of Campina do Monte Alegre – SP (Research, Society and Development, 2022)
This study aimed to analyze the relationship between market integration and the level of self-consumption with the food security of family farmers, having as an empirical universe the municipality of Campina do Monte Alegre in the State of São Paulo. In this sense, the Market Integration Index - IIM was used as a methodological instrument, whose purpose is to estimate the fractions of production destined for self-consumption or delivered to a market by the farmer. In the organization of results, the IIM was contrasted with the Brazilian Scale of Food Insecurity - EBIA per rural household and, in an accessory way, its relations with other socioeconomic variables that could potentially influence the level of food security were discussed.